Profile of patients with post partum hemorrhage in Dr. Soetomo Hospital, Surabaya, January 2011 - December 2013 - Mazaya Azyati; M. Aldika Akbar; Sudarno Sudarno (Majalah Obstetri dan Ginekologi, 2016)
Objectives: To recognize profile of patients with post partum haemorrhage in Dr. Soetomo Hospital, Surabaya, from January 2011 to December 2013.Materials and Methods: This was a descriptive study using secondary data from medical records of patients with postpartum hemorrhage at Dr. Soetomo Hospital in January 2011 - December 2013. Age, parity, origin, amount of hemoglobin, cause of postpartum hemorrhage, mode of delivery, and transfusion data patients were all recorded.Results: Result of this study were patient’s age, parity, origin, hemoglobin, cause of postpartum haemorrhage, mode of delivery, and transfusion data. From 202 cases, 131 patients (64.85%) were 20 – 35 years old, 134 patients (66.34%) were multipara, 84 patients (41.58%) were from private practice midwife, 70 patients’ (34.65%) hemoglobin were <8 gr%, 63 patients (31.19%) post partum haemorrhage caused by retained placenta, 164 patients (81.20%) labored with spontaneous way, and 131 patients (64.85%) did not receive transfusion.Conclusions: Most of the patients with postpartum hemorrhage were 20-35 years, multiparas, from private practice midwives, came with haemoglobin level <8 gr%, caused by retained placenta, delivered with spontaneous way, and did not receive transfusion.